2001
DOI: 10.1038/sj.bmt.1703198
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine and melphalan-based conditioning for patients with advanced hematological malignancies relapsing after a previous hematopoietic stem cell transplant

Abstract: Summary:Severe regimen-related toxicity often complicates second transplant procedures performed in patients with hematological malignancies that have relapsed after an initial hematopoietic stem cell (HSC) transplant. Therefore, we studied the safety and efficacy of a reduced-intensity fludarabine and melphalan based conditioning regimen in 11 patients who had relapsed following an autologous (n = 7) or allogeneic (n = 4) HSC transplant. All patients received allogeneic peripheral blood HSC from either an HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
(29 reference statements)
5
25
0
Order By: Relevance
“…We did not observe any cases of veno-occlusive disease of the liver (VOD) in the seven patients who received Mylotarg before URD HSCT, in contrast to the experience recently reported with this drug, describing a 17% incidence of VOD after HSCT, 11% fatal. 14 Mucositis was observed in 45% of our patients (Bearman grade 2); again, indirect comparison with MTX-based regimens in this respect is difficult due to intrinsic problems with mucositis grading systems, but one study using Flu/Mel and FK-506/MTX reported Bearman grade 2 stomatitis in nine of 11 patients (82%), 15 suggesting that the avoidance of MTX is important in minimizing regimen-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any cases of veno-occlusive disease of the liver (VOD) in the seven patients who received Mylotarg before URD HSCT, in contrast to the experience recently reported with this drug, describing a 17% incidence of VOD after HSCT, 11% fatal. 14 Mucositis was observed in 45% of our patients (Bearman grade 2); again, indirect comparison with MTX-based regimens in this respect is difficult due to intrinsic problems with mucositis grading systems, but one study using Flu/Mel and FK-506/MTX reported Bearman grade 2 stomatitis in nine of 11 patients (82%), 15 suggesting that the avoidance of MTX is important in minimizing regimen-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports confirm this observation. 3,15 It is expected that RIC regimens will allow a growing number of older and sicker patients with hematological malignancies to benefit from the life-saving potential of URD HSCT. Our encouraging 1-year DFS of 55% for the entire group, and 71% for patients with advanced AML or MDS seems comparable or better than standard dose regimens for younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bone Marrow Transplantation (2003) 32, 843-846. doi:10.1038/sj.bmt.1704225 Keywords: AML; APL; CNS-relapse; GvL Published data on second allogeneic transplants after leukaemia relapse indicate high treatment related mortalities (TRM) and relapse rates. [1][2][3][4] . In the most recently published series, a 2-year disease-free survival of 21% was found.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other studies found even higher incidences of fatal complications. 4 The high rate of TRM can be attributed to heavy pretreatment in most patients. For leukaemia relapse, the main reasons may be resistant disease and an insufficient graft-versus-leukaemia (GvL) effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation